Transformational Leadership Strategy in an Effort to Improve Employee Performance - I Made Adhitya Dwinata G; Ida Ayu Oka Martini (Green Publisher Indonesia, 2025)
This study investigates the impact of transformational leadership on employee performance at PT Bank Rakyat Indonesia (Persero) Tbk Kediri Tabanan Branch Office, particularly in the post-pandemic era. The research aims to explore how leadership strategies have influenced employee motivation, collaboration, and performance. A qualitative approach was adopted, using interviews with employees and management to gather data. The results reveal that transformational leadership, characterized by trust, motivation, clear communication, and support for individual development, has significantly improved employee performance. Leaders who demonstrate empathy and recognize employee contributions foster a motivated, loyal, and high-performing workforce. Additionally, an environment that encourages creativity and innovation, driven by transformational leadership, has facilitated better teamwork and organizational success. The study concludes that transformational leadership is crucial in enhancing employee performance and offers practical implications for organizations that implement effective leadership strategies to overcome post-pandemic challenges. The findings suggest that future leadership development programs should emphasize transformational leadership to sustain long-term improvements in employee performance.